Pancreatic Elastase Affects Liver Injury by Activating Pro-inflammatory Cytokines in Kupffer Cells via the JAK2/STAT3 Signaling Pathway - Feng, Ying; Jin, Xinxin; Xu, Haoyu; Sun, Bo; Guo, Meixia; Li, Minli (Current Molecular Medicine, 2025)
<span class=
Keywords: Kupffer cells